PENGARUH CUSTOMER EXPERIENCE DAN STORE ATMOSPHERE TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN PADA ER COFFEE PEKANBARU - Yudika Ananda; Jushermi Jushermi; Wasnury Rendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The rapid emergence of the cafe industry today has brought a new impact on consumers' lifestyles. One of the cafes in Pekanbaru City is Er coffee. This study aims to examine the effect of Customer Experience and Store Atmosphere on Customer Satisfaction and Customer Loyalty at Er coffee Pekanbaru. The analysis technique used is path analysis. The number of samples taken as many as 114 respondents using purposive sampling method. Data was collected by distributing questionnaires. Based on the results of the study, it was found that the Customer Experience variable and the Store Atmosphere variable had a significant effect on the Customer Satisfaction variable, the Customer Experience variable and the Store Atmosphere variable had a significant effect on the Customer Loyalty variable, the Customer Satisfaction variable had a significant effect on the Customer Loyalty variable, as well as the Customer Experience variable and the variable Store Atmosphere has a significant effect on Customer Loyalty through Customer Satisfaction.Keywords : Customer Experience, Store Atmosphere, Customer Satisfaction, Customer Loyalty.